Risk factors for injuries in football - Arnason, A.; Sigurdsson, S. B.; Gudmundsson, A.; Holme, I.; Engebretsen, L.; Bahr, R. (The American Journal of Sports Medicine, 2004)
Background: The injury risk in football is high, but little is known about causes of injury.